HUBUNGAN TINGKAT PENGETAHUAN WARGA TENTANG DEMAM BERDARAH DENGAN UPAYA PENCEGAHAN DEMAM BERDARAH DI DUKUH GUNUNG RT 01 RW 12 DESA PUCANGAN KECAMATAN KARTASURA KABUPATEN SUKOHARJO - Herminto, Budi; Diyono, Diyono; Kusumaningtyas, Windra (KOSALA : Jurnal Ilmu Kesehatan, 2015)
Background: Indonesia has a high risk of contracting dengue fever because it has spread to all regions. Dengue fever (DHF) is an infectious disease caused by dengue virus with the clinical manifestations of fever characterized by shock. The DHF cases is still occurred on Dukuh Gunung in Pucangan Kartasura Sukoharjo, it is caused the 3M plus program has not been implemented optimally and there has not been a study record how is the level of the villagers knowledge about the dengue disease.Objective: To determine the relationship between the level of the villagers knowledge about the dengue disease with the dengue fever prevention efforts on Dukuh Gunung Villagers of RT 01, RW 12 in Pucangan Kartasura, Sukoharjo.Research Design: This study is analytical research, designed by correlation and cross sectional approach. The study population was the head of all families in Dukuh Gunung RT 01, RW 12, Pucangan, Kartasura, Sukoharjo. Sample amount of 66 head of families. The sampling technique is random sampling. Datas were analyzed by chi square with SPSS 18.Research Result: (1) The average value of the villagers knowledge about the dengue fever is high category. (2) The average value of the dengue prevention efforts is good category. (3) The result of chi square test with p obtained 0,004 so, p < 0,05.Research conclusion: There is a significant relationship between the level of the villagers knowledge about the dengue disease with the dengue fever prevention efforts on Dukuh Gunung Villagers of RT 01, RW 12 Pucangan, Kartasura, Sukoharjo.Keyword :The levels of knowledge, The dengue fever, Prevention efforts